Lean Education: An Overview of Current Issues - Alves, Anabela Carvalho; Flumerfelt, Shannon; Kahlen, Franz-Josef.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This edited volume presents a structured approach to a new lean education curriculum, implemented for the education of engineers, managers, administrators as well as human resources developers. The authorship comprises professors and lecturers, trainers and practitioners who educate future professionals in Lean Thinking principles and tools. This edited book provides a platform for authors to share their efforts in building a Body of Knowledge (BoK) for Lean Education. The topical spectrum is state-of-the-art in this field, but the book also includes a glimpse into future developments. This is a highly informative and carefully presented book, providing valuable insight for scholars with an interest in Lean Education.
Introduction -- Lean Education for Applied Science Universities: a proposal by Federal Institutes of Applied Sciences in Brazil -- Lean Education in a University in the Philippines -- Using Student-Active Simulations in Lean Education -- Lean Teaching Experiences in Universidade NOVA de Lisboa and the TRIZ-LEAN Model -- Lean Learning at Oakland University -- Application of Lean Education in ECAM Lyon for development Lean Management Training -- Sawhney Lean Educational Maturity Model at the University of Tennessee Enhancing Lean Education -- Lean Education in the Faculty of Mechanical Engineering and Aeronautics of Rzeszow University of Technology, Poland -- Lean Education at University of Minho: aligning and pulling the right requirements geared on competitive industries -- Conclusions and new developments.
Keywords: Mechanical engineering; Psychology -- Methodology; Technology -- Sociological aspects; Mechanical Engineering; Psychological Methods; Science, Technology and Society